2019
DOI: 10.1088/1757-899x/687/2/022015
|View full text |Cite
|
Sign up to set email alerts
|

Effective non-destructive methods of evaluating quality of efficient building materials

Abstract: The research is devoted to the analysis of available and widely used conventional measures to ensure reliable operation of the in-situ reinforced concrete structures and their compliance with legal requirements. It requires using one of the research trends of the Samara school of material sciences developed by the authors some time ago. Several stages of the work have been distinguished during the process of defining methodological foundations for effective non-destructive methods. The first stage concerned th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Studies of the destruction processes of concrete carried out by the authors for a number of years [29][30][31] have shown that the nature and kinetics of concrete destruction processes are affected by two types of characteristics: the initial parameters of the concrete structure and the kinetic characteristics of the processes of its destruction. The first group includes such physical and mechanical characteristics of the structure of concrete as surface energy, modulus of elasticity, Poisson's ratio, compressive strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the destruction processes of concrete carried out by the authors for a number of years [29][30][31] have shown that the nature and kinetics of concrete destruction processes are affected by two types of characteristics: the initial parameters of the concrete structure and the kinetic characteristics of the processes of its destruction. The first group includes such physical and mechanical characteristics of the structure of concrete as surface energy, modulus of elasticity, Poisson's ratio, compressive strength.…”
Section: Resultsmentioning
confidence: 99%
“…The process of destruction of concrete, from the energy point of view, has three stages [29][30][31]. All three stages, which differ significantly from each other by the energy released during cracking.…”
Section: Methodsmentioning
confidence: 99%
“…For many years, the Academy of construction and architecture of Samara state technical university has been developing operational methods for determining the values of physical and mechanical characteristics of various materials by acoustic methods [7][8][9][10][11], as well as methods and techniques for optimal design of building structures [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. For concrete, the determination of frost resistance and water resistance are based on theoretical studies of the processes of destruction [27][28][29][30]. These theoretical studies of the energy concept and kinetic theory of fracture mechanics are based on the work of A.…”
Section: Methodsmentioning
confidence: 99%
“…A. Gifits and S. N. Zhurkova [31,33]. The developed methods of evaluation of physical and mechanical characteristics of concrete on the basis of ultrasonic studies are related to the methods of non-destructive testing [7][8][9][10][11][27][28][29][30]. The theoretical studies of the processes of concrete destruction by various types of external influences (compression, tension, bending, cyclic freezing, hydrostatic action), confirmed experimentally, have shown that the rate of concrete destruction and its durability depend on two groups of characteristics.…”
Section: Methodsmentioning
confidence: 99%